Pengaruh Brand Image terhadap Purchase Intention Dimediasi Oleh Brand Trust pada American Fastfood Dimasa Fenomena Boikot - Ketut Sunaryanto; Tika Lestari Noviyanti (MAMEN: Jurnal Manajemen, 2025)
The phenomenon of boycott against American Fastfood brands triggered by social issues has become a serious challenge in maintaining consumer Brand Trust and Purchase Intention. This study  aims to examine the influence of Brand Image, Brand Trust and Electronic Word Of Mouth on Purchase Intention during the boycott phenomenon. The research method used in Partial Lesat Square-Structured Equation Modeling (PLS-SEM). The method used in this study is quantitative methoid. The population in this study are customers of American fastfood brands in the Jabodetabek, so to meet the required sample, this study began with the distribution of questionnaires using Google Form. Validity and realiability test were carried out on 170 respondents. The findings in this study prove that the Electronic Word Of Mouth has no effect on Puchase Intention and data analysis shows that consumers exposed to boycott issues tend to have negative perceptions of the brands involved, so that it can damage Brand Image, reduce Brand Trust and ultimately affect Consumer Purchase Intention. The findings of this study contribute to management, especially in the fastfood industry, on the importancw of strengthening Brand Image and building Brand Trust consistently as the main strategy in maintaining Purchase Intention, especially amidst the boycott issue in the digital era. Consumers are now exposed to an overwhelming amount of online information, including reviews, comments, and influencer content. When information is overwhelming and unfiltered, consumers tend to be confused and unable to make decisions, resulting in eWOM losing its effectiveness in influencing purchase intentions.